Increased Expression of CCAT2 LncRNA in Non-Melanoma Skin Cancer - Sadeghi Dehcheshmeh 1, Iman; Masoomi Karimi 2, Masoomeh; Jafarisani 3*, Moslem (Shahroud Journal of Medical Sciences, 2018)
Background: The non-melanoma skin cancer is one of the most prevalent type of skin cancers, which at least involves 2-3 million people annually. In recent decades, we have witnessed a considerable rise in the incidence of NMSC in Iran. In this paper, we studied the expression of the new lncRNA colon cancer-associated transcript 2 (CCAT2) in cases of non-melanoma skin cancer (NMSC).Methods: The sample included 36 patients and 30 healthy subjects, of whom, we extracted the total RNA from tissues. Using the cDNA synthase, we conducted the real time PCR. Using the SPSS software, we analyzed the data and drew the graphs by PRISM software. The index of P<0.05 was considered significant.Results: The values of CCAT2, TCF7L2 and MYC indicated a considerable expression rise in the NMSCs in comparison with the controls. In addition, the expression of CCAT2 was found to be higher in high-grade tumors than low-grade tumors. According to results, there is a relationship between CCAT2 and NMSC initiation as well as the progression. The CCAT2 functions by its downstream genes, TCF7L2 and MYC, with an impact on the Wnt signaling pathway.Conclusions: based on the results, the lncRNA CCAT2 acts as a potential biomarker for NMSC pathogenesis.